Knockout of miR‐184 in zebrafish leads to ocular abnormalities by elevating p21 levels. Issue 5 (22nd April 2023) - Zhang, Jing; Li, Ping; Sun, Luqian; Jiang, Ning; Guo, Wenya; Wang, Jungai; Gao, Fen; Li, Jing; Li, Hui; Zhang, Jun; Mu, Hongmei; Hu, Yanzhong; et al.
Abstract: miR‐184 is one of the most abundant miRNAs expressed in the lens and corneal tissue. Mutations in the seed region of miR‐184 are responsible for inherited anterior segment dysgenesis. Animal models recapitulating miR‐184‐related anterior segment dysgenesis are still lacking, and the molecular basis of ocular abnormalities caused by miR‐184 dysfunction has not been well elucidated in vivo. In the present study, we constructed a miR‐184 −/− zebrafish line by destroying both two dre‐mir‐184 paralogs with CRISPR‐Cas9 technology. Although there were no gross developmental defects, the miR‐184 −/− zebrafish displayed microphthalmia and cataract phenotypes. Cytoskeletal abnormalities, aggregation of γ‐crystallin, and lens fibrosis were induced in miR‐184 −/− lenses. However, no obvious corneal abnormalities were observed in miR‐184 −/− zebrafish. Instead of apoptosis, deficiency of miR‐184 led to aberrant cell proliferation and a robust increase in p21 levels in zebrafish eyes. Inhibition of p21 by UC2288 compromised the elevation of lens fibrosis markers in miR‐184 −/− lenses. RNA‐seq demonstrated that levels of four transcriptional factors HSF4, Sox9a, CTCF, and Smad6a, all of which could suppress p21 expression, were reduced in miR‐184 −/− eyes. The predicted zebrafish miR‐184 direct target genes (e.g., atp1a3a and nck2a) were identified and verified in miR‐184 −/− eye tissues. The miR‐184 −/− zebrafish is the first animal model mimicking miR‐184‐related anterior segment dysgenesis and could broaden our understanding of the roles of miR‐184 in eye development. Abstract : A miR‐184 knockout zebrafish line was constructed with CRISPR‐Cas9 technology. The miR‐184 −/− zebrafish displayed microphthalmia due to aberrant cell proliferation induced by elevated p21 levels. Knockout of miR‐184 disturbed lens cytoskeleton and crystallin homeostasis and led to cataract formation. Inhibition of p21 compromised the induced lens fibrosis in miR‐184 −/− lenses. The miR‐184 −/− zebrafish is the first animal model mimicking miR‐184‐related anterior segment dysgenesis.